Therapeutic potential of resveratrol through ferroptosis modulation: insights and future directions in disease therapeutics - Peng, Liu; Hu, Xi-Zhuo; Liu, Zhi-Qiang; Liu, Wen-Kai; Huang, Qun; Wen, Yue (Frontiers in Pharmacology, 2024)
Resveratrol, a naturally occurring polyphenolic compound, has captivated the scientific community with its promising therapeutic potential across a spectrum of diseases. This review explores the complex role of resveratrol in modulating ferroptosis, a newly identified form of programmed cell death, and its potential implications for managing cardiovascular and cerebrovascular disorders, cancer, and other conditions. Ferroptosis is intricately linked to the pathogenesis of diverse diseases, with resveratrol exerting multifaceted effects on this process. It mitigates ferroptosis by modulating lipid peroxidation, iron accumulation, and engaging with specific cellular receptors, thereby manifesting profound therapeutic benefits in cardiovascular and cerebrovascular conditions, as well as oncological settings. Moreover, resveratrol's capacity to either suppress or induce ferroptosis through the modulation of signaling pathways, including Sirt1 and Nrf2, unveils novel therapeutic avenues. Despite resveratrol's limited bioavailability, advancements in molecular modification and drug delivery optimization have amplified its clinical utility. Future investigations are poised to unravel the comprehensive mechanisms underpinning resveratrol's action and expand its therapeutic repertoire. We hope this review could furnish a detailed and novel insight into the exploration of resveratrol in the regulation of ferroptosis and its therapeutic prospects.